2020
DOI: 10.1093/geroni/igaa057.1194
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Cognitive-Behavioral Therapy for Depression: A Feasibility Study for Homecare Older Adults

Abstract: This pilot study examined the feasibility of delivering internet-based cognitive behavioral therapy (iCBT) to homebound older adults with symptoms of depression who are recipients of non-medical home care. A feasibility open trial was conducted in the homes of homecare older adults (n=26). When possible, home care workers (HCWs) of older adults (n=13) were recruited to provide external support for iCBT usage. In cases where consistent assistance from the same HCW was not feasible, participants were given the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…However, iCBT intervention groups with clinician guidance had the most remarkable improvement of QoL, when compared to selfguided iCBT sample groups, which had the lowest QoL improvements (Montero-Marín et al, 2016;Xiang et al, 2020).There was no statistically significant difference in QoL outcomes between groups with clinician guidance via scheduled telephone sessions compared to clinician guidance via e-mail correspondence (Farrer et al, 2012;Lindner et al, 2014). Additionally, synchronous clinician-guided iCBT improved the social functioning components of QoL scoring compared to asynchronous iCBT clinician-guided sessions (Dobkin et al, 2021;Johansson et al, 2012).…”
Section: Social Domainmentioning
confidence: 92%
See 3 more Smart Citations
“…However, iCBT intervention groups with clinician guidance had the most remarkable improvement of QoL, when compared to selfguided iCBT sample groups, which had the lowest QoL improvements (Montero-Marín et al, 2016;Xiang et al, 2020).There was no statistically significant difference in QoL outcomes between groups with clinician guidance via scheduled telephone sessions compared to clinician guidance via e-mail correspondence (Farrer et al, 2012;Lindner et al, 2014). Additionally, synchronous clinician-guided iCBT improved the social functioning components of QoL scoring compared to asynchronous iCBT clinician-guided sessions (Dobkin et al, 2021;Johansson et al, 2012).…”
Section: Social Domainmentioning
confidence: 92%
“…Nine studies compared iCBT with passive comparators such as treatment as usual or waitlist controls (Berger et al, 2011;Burton et al, Individual group sample sizes ranged from 14 (Burton et al, 2016) to 1843 (Donker et al, 2013). All studies recruited male and female participants, with mean ages ranging from 35 (Burton et al, 2016) to 76.4 (Xiang et al, 2020).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
See 2 more Smart Citations
“…Mental health support refers to any type of support aimed at protecting or promoting psychosocial well-being [5], such as therapy, education, and health promotion programs. Recent reviews have demonstrated the effectiveness of digital health interventions in reducing social isolation and depression in older adults [6][7][8][9]. However, older adults may experience several barriers to accessing and using digital health resources, such as lack of knowledge and awareness of digital health resources, little exposure to and experience with technology in general, and lack of confidence in using a computer [10].…”
Section: Potential Of Digital Mental Health Interventionsmentioning
confidence: 99%